Improving growth potential in Senegalese sole (Solea senegalensis) through dietary protein - Canada, Paula (2020)
In the present work, recent studies that contributed for improving dietary protein in practical microdiets for Senegalese sole larvae are revised, in an attempt to overcome some of the current problems in this species larviculture, such as the difficult early adaptation to inert diets and highly variable growth rates. Different diet formulation strategies were employed in an attempt to improve Senegalese sole larvae capacity to utilize and deposit protein throughout metamorphosis, to further maximize growth potential: (1) increasing indispensable amino acids (IAA) content (2) meeting the ideal IAA profile by adjusting the dietary AA profile to the larval body AA profile and (3) decreasing the complexity (molecular weight) of dietary protein to increase its digestibility. Either manipulating the quality or the complexity of dietary protein had impact on the larvae capacity to utilize protein and direct it for growth. Sole larvae seem to be able to adapt their digestive functions and metabolic capacity to dietary protein. Moreover, increasing the dietary IAA/DAA ratio and changing the degree of hydrolysis of dietary protein affected the expression pattern of muscle growth related genes, with consequences on muscle cellularity and potential for growth. The expression of DNA methyltransferases was altered in response to changes in dietary protein. The novelty of such information in fish may trigger further studies on the effect of dietary protein on the epigenetic regulation of growth. In conclusion, optimal protein quality for Senegalese sole seems to change during larval development. Whereas the inclusion of a moderately hydrolysed protein comes up as a promising way to improve growth in early larval stages, larger peptides and intact protein seem to be more suitable to sole post-larvae and young juveniles. Therefore, these results suggest that dietary protein fraction formulation of microdiets for Senegalese sole should be adapted to each developmental stage, what has important consequences for practical larval microdiets formulation and feeding protocols.